The Role of Authentic Leadership and Organizational Commitment to Reduce Turnover Intention in Digital Company - Ahmad Azmy; Sina Mauludi (Bina Nusantara University, 2024)
The research analyzed the relationship between authentic leadership, organizational commitment, and turnover intention. The problem was that technology companies experienced an increase in turnover intention. It was unique in analyzing the causality of turnover intention through aspects of leadership and commitment. The research analyzed the direct and indirect effects of reducing turnover, conducted on digital companies operating in the consulting services sector. Purposive sampling was used as a sampling technique. Data collection was carried out using a questionnaire distributed via Google Forms with a total of 111 respondents. The research findings indicate that authentic leadership influences organizational commitment. Furthermore, organizational commitment has a negative influence on turnover intention. In addition, the indirect effect of authentic leadership on turnover intention is mediated by organizational commitment. Hence, it is essential for companies to increase employee commitment throughout the organization. Business organizations must pay attention to the phenomenon of turnover instruction. Meanwhile, employee turnover has a negative effect on the quality of business processes. The turnover instruction problem is a classic problem faced by every company. Aspects of leadership and organizational commitment must be the main factors in reducing turnover. The long-term success of a business is determined by the contribution and productivity of its employees. Turnover intentions can be reduced through implementing authentic leadership and consistently increasing organizational commitment.